Achromatic Fresnel Lens with Improved Efficiency for PV Systems - Mario González Montes; Juan Carlos Martínez-Antón; Daniel Vázquez Moliní; Antonio Álvarez Fernandez-Balbuena; E. Bernabeu (International Journal of Photoenergy)
This work is aimed to design and evaluate different achromatic Fresnel lens solutions capable of operating as concentrators aimed at photovoltaic cells systems. Throughout this study, the theoretical parametric design of the achromatic lens will be shown together with a series of simulations to verify the performance of each lens topology. The results will be compared with a standard Fresnel lens to ascertain the validity and effectiveness of the obtained design. Finally, a novel kind of hybrid lens is proposed, which combines the advantages of each type of lens (standard and Fresnel) according to the optimal operating region of each design. Efficiency and concentration ratios of each particular lens are shown, regarding lens dimension, light’s incidence angle, or wavelength. Through this innovative achromatic design concentration ratios above 1000 suns, which hardly reach standard Fresnel lenses. Furthermore chromatic dispersion is minimized and the efficiency rate is over 85% of efficiency for a wide spectral range (from 350 nm to 1100 nm).